2018
DOI: 10.1093/sleep/zsy137
|View full text |Cite
|
Sign up to set email alerts
|

LAT1-like transporters regulate dopaminergic transmission and sleep in Drosophila

Abstract: Amino acid transporters are involved in functions reportedly linked to the sleep/wake cycle: neurotransmitter synthesis and recycling, the regulation of synaptic strength, protein synthesis, and energy metabolism. In addition, the existence of bidirectional relationships among extracellular content, transport systems, and sleep/wake states is receiving emerging support. Nevertheless, the connection between amino acid transport and sleep/wake regulation remains elusive. To address this question, we used Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Dopamine was increased by feeding flies the dopamine precursor Levodopa (L-Dopa) 54,55 . As seen in Figure 7A, feeding 20day old flies L-DOPA disrupted nighttime sleep as previously reported 56,57 . Importantly, spatial learning was restored in 20-day old, L-Dopa fed flies compared to their age-matched vehicle-fed siblings ( Figure 7B).…”
Section: Enhancing Dopamine Signaling Reverses Age Dependent Cognitivsupporting
confidence: 85%
“…Dopamine was increased by feeding flies the dopamine precursor Levodopa (L-Dopa) 54,55 . As seen in Figure 7A, feeding 20day old flies L-DOPA disrupted nighttime sleep as previously reported 56,57 . Importantly, spatial learning was restored in 20-day old, L-Dopa fed flies compared to their age-matched vehicle-fed siblings ( Figure 7B).…”
Section: Enhancing Dopamine Signaling Reverses Age Dependent Cognitivsupporting
confidence: 85%
“…Furthermore, JH Inducible-21 (JHI-21) has been reported to be required for sleep/wake regulation, since downregulation of JhI-21 in dopaminergic neurons reduced the sensitivity to L-DOPA, thus leading to an increase in daily sleep and sleep bout duration during the night. (Aboudhiaf et al, 2018). Correspondingly, our previous work found that Wolbachia could stimulate the JH signaling pathway in male Drosophila (Liu et al, 2014).…”
Section: The Effect Of Wolbachia On the Sleep Behavior Of Hostsmentioning
confidence: 80%
“…In fact, glycine or D-serine acts as a co-agonist of N-methyl-D-aspartate receptors (NMDARs) and promotes sleep through the sub-type of ionotropic glutamate receptors (Dai et al, 2019; Kawai et al, 2015; Tomita et al, 2015). Emerging evidence further supports the roles of amino acid transporters and metabolic enzymes in sleep regulation (Aboudhiaf et al, 2018; Sonn et al, 2018; Stahl et al, 2018). In particular, we have demonstrated that starvation induces the expression of metabolic enzymes for serine biosynthesis in Drosophila brains, and elevates free serine levels to suppress sleep via cholinergic signaling (Sonn et al, 2018).…”
Section: Introductionmentioning
confidence: 82%